The coronavirus outbreak and the remote work implementation for not urgent judicial processes, the Peruvian case - Tapia Coba, Fany Mavel (2020)
This article gives an overview of the implementation of remote work system that have transformed the judicial system during the context of coronavirus outbreak. The implementation of Remote work serves to optimize the procedural discharges of not urgent Judicial Processes. It is perceived that remote work is relevant to the Judicial Court optimization and it can be adapted in the places where an Electronic Judicial Expedient is not available.